A Soft Transporter Robot Fueled by Light. Issue 5 (20th January 2020) - Pilz da Cunha, Marina; Ambergen, Sebastiaan; Debije, Michael G.; Homburg, Erik F. G. A.; den Toonder, Jaap M. J.; Schenning, Albert P. H. J.
Abstract: Mobile organisms with ability for locomotion and transportation, such as humans and other animals, utilize orchestrated actuation to perform actions. Mimicking these functionalities in synthetic, light‐responsive untethered soft‐bodied devices remains a challenge. Inspired by multitasking and mobile biological systems, an untethered soft transporter robot with controlled multidirectional locomotion with the ability of picking up, transporting, and delivering cargo driven entirely by blue light is created. The soft robot design is an ensemble of light‐responsive liquid crystalline polymers that can harness motion either collectively or individually to obtain a high degree of motion control for the execution of advanced tasks in a dry environment. Through orchestrated motion of the device's "legs", single displacement strides, which exceed 4 mm and can be taken in any direction, allow for locomotion around objects. Untethered cargo transportation is demonstrated by a pickup and release mechanism using the device's "arms". This strategy demonstrates the constructive harnessing of orchestrated motion in assemblies of established actuators, performing complex functions, mimicking constructive behavior seen in nature. Abstract : Soft robotic devices strive to mimic the multidirectional locomotion and transportation performed by living creatures. Here, an untethered polymer device is shown to achieve macroscopic functions including grasping, carrying, walking, and releasing of objects performed and controlled solely with light. The functions are completed through constructive orchestrated motion of multiple liquid crystalline actuators that compose the soft robotic device.